Effect of Extracellular Marennine produced by Haslea Ostrearia on the Blood Clams Tegillarca Granosa - Bachtiar, Eri; Ajeng Dinda Lestari; Astuty, Sri; Sunarto, Sunarto; Prasetiya, Fiddy Semba (Department of Aquaculture, 2024)
Marennine is a blue-green pigment produced by diatoms of the Haslea genus, one of which is Haslea ostrearia. This marennine pigment is water-soluble and confirmed to contain polyphenols and glycosides. There are two forms of marennine pigment: the intracellular form of marennine (IMn) and the extracellular form of marennine (EMn). Marennine pigments exhibit various biological activities such as antibacterial, antiviral, antioxidant, allelopathic, and inhibiting the growth of other diatoms. With this biological activity, marennine can be used in various fields, one of which is aquaculture.This research aims to determine the level of toxicity and analyze the effect of exposure to the extracellular marennine produced by H. ostrearia on the juvenile blood clam Tegillarca granosa. By using the toxicity test method, Blue water which is supernatant of H. ostrearia (BW) was tested on juvenile of commercially important bivalve species, the blood clams Tegillarca granosa, with three treatments, namely control (0 mg/L), treatment A (0.25 mg/L) and treatment B (0.5 mg/L of BW). The observation parameters of this study were LC50-72 h with one-way ANOVA analysis. The results showed that the BW produced by H. ostrearia increased the survival of juvenile blood clams T. granosa up to 27.7% in treatment B (0.5 mg/L) compared to control within 72 h. The one-way ANOVA analysis revealed that the control and treatment B (0.5 mg/L) were significantly different. This study shows that there is potential to develop the use of marennine in shellfish aquaculture.